A bibliometric review of research on entrepreneurial capacity for the period 1979 to 2022: Current status, development, and future research directions - Meghna Chhabra; Rohail Hassan; Mohd Asif Shah; Richa Sharma (Cogent Business & Management, 2023)
This study deals with the primary areas and the present dynamics related to entrepreneurial capacity (EC); apart from this, it provides research directions in EC's research field that would be of use in the future. With the aid of bibliometric analysis, we analysed Google Scholar, Scopus, and the ISI Web of Science databases and arrived at 193 studies that we use as samples; these studies enable us to recognise the research activity conducted on EC from 1979 to 2022. The most influential articles and authors have been identified based on their publications, citations, location, and importance within the network. Apart from this, we investigate current themes, discover barriers to development in literature, and provide ways for future research. Although research activity on EC occurs globally, there is a shortage of studies concerning developing countries' context; countries experience a lack of collaboration, which is observed explicitly between the authors of developing and developed countries. This research focuses on broadly two themes: entrepreneurship education (EE) as an antecedent of EC, which, in turn, is an antecedent to entrepreneurial intention (EI), and EC as an antecedent factor of firm performance and economic growth. Interestingly, there is also a rising focus on Entrepreneurial Universities. We conclude by suggesting potential research directions.
Keywords: 650; economic growth; entrepreneurial capacity; entrepreneurial intention; entrepreneurship education; review